The efficacy of shoe modifications and foot orthoses in treating patients with hallux rigidus: a comprehensive review of literature - Colò, Gabriele; Fusini, Federico; Samaila, Elena Manuela; Rava, Alessandro; Felli, Lamberto; Alessio-Mazzola , Mattia; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2020)
Hallux rigidus (HR) is a degenerative disease of the first metatarsophalangeal (MTP1) joint and affects about 2.5% of people older than 50 years. The real etiology of this condition remains under debate. Clinical symptoms, physical exam, and instrumental evidence are important in assessing and grading the disease. The anatomy of the first metatarsal is unique and its configuration may play a significant role in the HR development. The first approach usually begins with shoe modifications and foot orthoses, designed to limit irritation from the dorsal osteophytes, reducing motion and the mechanical stresses on the joint. To prevent or delay the development of HR, shoes should be sufficiently long, comfortable, with high toe box and broad toe-boxed, and should bear an allowed space for the orthotic device. The ideal orthotic appears to require a 3-mm thickness with a correct stiffness, and also increasing and extending the medial metatarsal arch just proximal to the metatarsal head, raising the first metatarsal and allowing the proximal phalanx to rest in a more plantarflexed position, decompressing the dorsal aspect of the joint. The increased foot pronation moment with medial column overload should be corrected. In addition, the maximum follow-up found by the analyzed studies was of 14.4 years, so the Authors cannot conclude how long conservative care can keep a patient free from pain and able to perform normal daily activities. However, the use of shoe modifications and foot orthoses may be considered a safe treatment and then should be always offered to patients.